DATA SECURITY ON CLOUD COMPUTING (INDIAN JOURNAL OF INFORMATION TECHNOLOGY (INDJIT), 2019)
Cloud computing is an Internet-based computing. It has received attention in recent years but security issue is one of the major inhibitor in decreasing the growth of cloud computing